Czynniki kreujące poziom wybranych składników pokarmowych w mleku krów, mające wpływ na atrakcyjność dietetyczną = The factors which are create the level of selected nutrients in milk of Holestin Fresian cows that affect the attractiveness of the diet - Duszyńska-Stolarska, Oliwia; Górecka, Milena; Habel, Angelika; Bogdzińska, Maria (Journal of Education, Health and Sport, 2015)
Duszyńska-Stolarska Oliwia, Górecka Milena, Habel Angelika, Bogdzińska Maria. Czynniki kreujące poziom wybranych składników pokarmowych w mleku krów, mające wpływ na atrakcyjność dietetyczną = The factors which are create the level of selected nutrients in milk of Holestin Fresian cows that affect the attractiveness of the diet. Journal of Education, Health and Sport. 2015;5(6):258-266. ISSN 2391-8306. DOI 10.5281/zenodo.18559 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A258-266 https://pbn.nauka.gov.pl/works/565795 http://dx.doi.org/10.5281/zenodo.18559 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 14.06.2015. Czynniki kreujące poziom wybranych składników pokarmowych w mleku krów, mające wpływ na atrakcyjność dietetyczną The factors which are create the level of selected nutrients in milk of Holestin Fresian cows that affect the attractiveness of the diet Oliwia Duszyńska-Stolarska, Milena Górecka, Angelika Habel, Maria Bogdzińska1 Zakład Genetyki i PodstawHodowli Zwierząt Uniwersytet Technologiczno-Przyrodniczy im. Jana i Jędrzeja Śniadeckichw Bydgoszczy1 Streszczenie Obecnie konsumenci poszukują mleka o wysokiej zawartości białka oraz niskim poziomie tłuszczu. Stworzenie takiego produktu stawia przed hodowca nie lada wyzwanie. Opłacalna hodowla jest również związana z wysoka wydajnością mleczną. Jednakże pozyskanie znacznych ilości mleka o wysokiej jakości jest celem trudnym w realizacji. Badania dowodzą iż czynniki środowiskowe takiej jak system utrzymania, żywienie czy kolejna laktacja mogą w znacznym stopniu wpływać na ilość oraz jakość pozyskiwanego mleka. W przypadku odpowiedniego żywienia mleko może być wzbogacone o substancje korzystne dla zdrowia. Wraz z rozwojem nauki możliwości oceny zwierząt pod względem ich produkcyjności również rosną. Cechy związane z mlecznością są uwarunkowane genetycznie. Badania nad polimorfizmem określonych genów pozwala na określenie tych genotypów które warunkują najkorzystniejszą wartość cechy. Słowa kluczowe: wydajność mleczna, składniki odżywcze, czynniki środowiskowe, polimorfizm genów, krowy rasy Holsztyńsko-Fryzyjskiej. Summary Currently, consumers are looking for milk with a high protein content and a low level of fat. The creation of such a product is great challenge for a breeder. Profitable animal husbandry is also associated with high milk yield. However, obtaining significant quantities of high quality milk is a difficult goal to achieve. Research shows that environmental factors such as system maintenance, nutrition or another lactation can significantly affect the quantity and quality of the acquired milk. In the case of adequate nutrition milk it may be enriched with substances beneficial to health. With the development of science the possibility to assess the animals for their productivity also increase. Features associated with milk production are genetically determined. Research on polymorphism of certain genes allows for identification of those genotypes that determine the most favorable value characteristics. Key words : milk yield, nutrient, environmental factors, polymorphism of genes, Holestin-Fresian cow.